The influence of laparoscopic vs. open gastric bypass on hemodynamic function in morbidly obese patients during general anesthesia - Gaszynski, Tomasz (Termedia Publishing House, 2014)
INTRODUCTION: The open or laparoscopic procedure has an important influence on the hemodynamic function in morbidly obese patients undergoing bariatric surgery. The anesthesiologist and surgeon must be aware of changes in hemodynamic performance during laparoscopy or laparotomy under general anesthesia. AIM: To evaluate and compare the hemodynamics in two types of surgery: open vs. laparoscopic. MATERIAL AND METHODS: After obtaining the local ethics committee approval 60 morbidly obese (MO) patients (body mass index ≥ 40 kg/m(2)) scheduled for elective open or laparoscopic Roux-en-Y gastric bypass were included. Patients were allocated to study groups depending on the scheduled type of surgery (no randomization). General anesthesia with sevoflurane was performed. The hemodynamic parameters were recorded using a HemoSonic 100 device – a transesophageal Doppler measurement at time points: T1 – initial, T2 – after creating pneumoperitoneum (group PP) or opening the abdomen (group OP). RESULTS: Complete data were collected on 28 patients in group LP and 21 in group OP. There was no statistical difference between groups in demographic data. At time point T2 in both groups the parameters stroke volume, peak velocity and cardiac index decreased, and total systemic vascular resistance increased significantly compared to T1 (p < 0.05). In group LP the parameters cardiac output and acceleration (Acc) of blood decreased significantly compared to T1 (p < 0.05). There were significant differences between groups (p > 0.05) in cardiac output, total systemic vascular resistance and Acc, which were significantly higher in the OP group. In both groups mean arterial pressure increased and heart rate stayed similar to T1 with no significant difference (p > 0.05). No complications were observed. CONCLUSIONS: Pneumoperitoneum has a significant negative influence on hemodynamic function during laparoscopic bariatric procedures compared to open surgery in morbidly obese patients.